Voltage Regulation in Excessive Penetration of Solar Rooftop Distribution System Using Battery Energy Storage System - Sokul, Suwicha; Fangsuwannarak, Thipwan; Chayakulkheeree, Keerati (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2023)
This paper presents the methodology and solutions for mitigating voltage variation under steady conditions caused by differing levels of PV penetration in low-voltage (LV) rural networks. The LV rural area of the Provincial Electricity Authority (PEA) North-East area 3 District of Thailand is used as a case study with load profiles from Geographic Information System (GIS) software. Moreover, rooftop PV power generation is calculated using recorded data on irradiation in Nakhon Ratchasima Province. DIgSILENT Power Factory software is used to simulate and analyze the quality of the proposed method by focusing on the voltage level at the end of the line or dead-end (DE) of the LV network. The results show overvoltage at the DE under the high rooftop PV penetration. The battery energy storage system (BESS) is applied to mitigate the problem of low quality. Meanwhile, the system is operated by examining load demand and rooftop PV power generation to define the state of charging and discharging conditions. The proposed method can be integrated into the algorithm of a rooftop PV system and BESS local control in the home energy management system (HEMS). The results show that the proposed method can reduce the voltage variation problem existing in the PEA standard while improving the voltage level at all DEs.